Posisi Anak Angkat Dalam Pandangan Norma Ilahi Dan Norma Hukum - Dhiauddin Tanjung, Azhar, (Pusdikra Publishing, 2024)
The position of adoption in view of Divine Norms and Legal Norms discusses its meaning, its position in Divine Norms, its position in Legal Norms, namely discussing the Presidential Regulation concerning it, RI Legal Norms No. 23 of 2002 concerning its Position, Legal Norms 45, and others. The biological father of the adoptee is a legal guardian who is related to him by blood (his blood relationship), while the father who is not related by blood is someone else such as his adoptive father and mother. The adoptive father is someone else as explained above, the adoptive father is not blood related to him.